Social transfer of alcohol withdrawal-induced hyperalgesia in female prairie voles. (2nd November 2018) - Walcott, Andre T.; Smith, Monique L.; Loftis, Jennifer M.; Ryabinin, Andrey E.
ABSTRACT: The expression of pain serves as a way for animals to communicate potential dangers to nearby conspecifics. Recent research demonstrated that mice undergoing alcohol or morphine withdrawal, or inflammation, could socially communicate their hyperalgesia to nearby mice. However, it is unknown whether such social transfer of hyperalgesia can be observed in other species of rodents. Therefore, the present study investigated if the social transfer of hyperalgesia occurs in the highly social prairie vole ( Microtus ochrogaster) . We observe that adult female prairie voles undergoing withdrawal from voluntary two-bottle choice alcohol drinking display an increase in nociception. This alcohol withdrawal-induced hypersensitiity is socially transferred to female siblings within the same cage and female strangers housed in separate cages within the same room. These experiments reveal that the social transfer of pain phenomenon is not specific to inbred mouse strains and that prairie voles display alcohol withdrawal and social transfer-induced hyperalgesia.